Evaluation system model for remote control software - Bonillo, Pedro (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This article aims to describe a system model for software tools evaluation. Software evaluation is commonly associated to a checklist that verifies the existence of some relevant characteristics involved in the use of software. Some other key factors of software evaluation that are taken into account are: the context and the whole process in which software is involved before being applied by the users, and the evaluator's standpoint. In this evaluation process, the entities, attributes, and relationships that mainly affect to the organization are integrated. All this suggested the use of a system model through which the evaluation could be modeled as an open system. This research establishes the relationships as well as the required conditions between the systemic thought and the evaluation perspective, into a model that allows both an acceptable estimation and a set of premises to evaluate successfully software use towards the framework of business interests by taking as a study case, the remote control software tools of the internal support organization of CANTV, a Venezuelan communications firm.